2005
DOI: 10.5194/nhess-5-425-2005
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of multi-temporal remote sensing images to characterize landslide slip surface ‒ Application to the La Clapière landslide (France)

Abstract: Abstract. Landslide activity is partly controlled by the geometry of the slip surface. This activity is traduced at the surface by displacements and topographic variations. Consequently, multi-temporal remote sensing images can be used in order to characterize the geometry of landslide slip surface and its spatial and temporal evolution. Differential Digital Elevation Models (DEMs) are obtained by subtracting two DEMs of different years. A method of multi-temporal images correlation allows to generate displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 24 publications
(38 reference statements)
0
58
0
9
Order By: Relevance
“…This methodology has been used to measure displacements not only for landslides (Delacourt et al, 2004(Delacourt et al, , 2007Casson et al, 2005) but also for earthquakes (Van Puymbroeck et al, 2000) and for glacier flows (Kääb, 2002;Berthier et al, 2005). The capability of DIC (Digital Image Correlation) to monitor landslide surfaces over multiple time steps has been demonstrated with aerial photographs (Casson et al, 2005) and Terrestrial Optical Photogrammetry (Sturzenegger and Stead, 2009;Travelletti et al, 2012). Only a few studies have reported the usefulness of satellite images in this field (Delacourt et al, 2007(Delacourt et al, , 2009; Leprince et al, 2008) and exhaustive research addressing to the analysis of longer available very high resolution (VHR) satellite time series is still missing.…”
Section: Tofani Et Al: Use Of Remote Sensing For Landslide Studiementioning
confidence: 99%
“…This methodology has been used to measure displacements not only for landslides (Delacourt et al, 2004(Delacourt et al, , 2007Casson et al, 2005) but also for earthquakes (Van Puymbroeck et al, 2000) and for glacier flows (Kääb, 2002;Berthier et al, 2005). The capability of DIC (Digital Image Correlation) to monitor landslide surfaces over multiple time steps has been demonstrated with aerial photographs (Casson et al, 2005) and Terrestrial Optical Photogrammetry (Sturzenegger and Stead, 2009;Travelletti et al, 2012). Only a few studies have reported the usefulness of satellite images in this field (Delacourt et al, 2007(Delacourt et al, , 2009; Leprince et al, 2008) and exhaustive research addressing to the analysis of longer available very high resolution (VHR) satellite time series is still missing.…”
Section: Tofani Et Al: Use Of Remote Sensing For Landslide Studiementioning
confidence: 99%
“…Jusqu'à présent, les images satellitaires étaient privilégiées bien qu'elles présentent des limitations en termes de résolution spatiale restreinte malgré les progrès récents, de couverture nuageuse, ou bien d'heure locale d'acquisition fixe, ... . L'utilisation de plates-formes aéroportées résout en partie ces problèmes puisqu'elles permettent d'obtenir des données avec une résolution spatiale inférieure à 50 cm (CASSON et al, 2005). De plus, la télédétection aérienne permet l'acquisition de couples stéréoscopiques à partir desquels des Modèles Numériques de Terrain (MNT) de précision submétrique peuvent être calculés.…”
Section: Introductionunclassified
“…Pour lever ces dernières limitations, de nouvelles techniques sont mises en oeuvre. Des plates-formes de tailles réduites, telles que des cerf-volants, des ballons et des drones apparaissent dors et déjà comme des outils très prometteurs pour les levés topographiques de glissements de terrain ou d'érosion de pentes (CASSON et al, 2005 ;JACOME et al, 2009), de rivières (LEJOT et al, 2007, mais également pour la surveillance des cultures (SUGIURA et al, 2005). Ces plates-formes sont d'une utilisation très flexible et permettent, pour un coût modéré, d'effectuer des levés répétés à périodicité variable (hebdomadaire à annuelle).…”
Section: Introductionunclassified
“…The displacement field of slow to moderate velocity landslides (1.5 m/year < v < 1.5 m/month, [1]) is a fundamental parameter to measure, for both applied and research purposes [2][3][4][5]. If followed for a long period of time and coupled with measurements of external parameters such as rainfall or seismic activity, the displacement field can constrain numerical models of landslide evolution [6,7] and is also essential for risk mitigation.…”
Section: Introductionmentioning
confidence: 99%